Economía - EN22 - 202302 - Castro Herrera, Soraya Beatriz (2023)
Description: Economics is an introductory theoretical and practical course in microeconomics and macroeconomics. Along the course, the student will understand main microeconomics concepts: demand, supply and market equilibrium; production and cost functions; elasticity; price controls; monopoly; oligopoly and basic macroeconomics concepts: GDP, growth, unemployment, inflation. Purpose: The course aims to contribute the students understanding of economic principles using them in every day decisions and in simulated situations. It focuses in the Level 1 development of General Competences of Critical Thinking, and Quantitative Reasoning.